Pengaruh Suplementasi SOYXYL & Kolin Klorida dalam Pakan Terhadap Utilitas Konsumsi Pakan Total, Hijauan, dan Konsentrat Sapi Potong Brahman Cross (Bos indicus) - Raditya Nandhirabrata; Widiyanto Widiyanto; Bambang Waluyo Hadi Eko Prasetiyono (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study aimed to determine whether the treatments applied had an effect on average daily gain, total feed intake, and total feed digestibility of beef cattle supplemented with bypass protein under the commercial name “Soyxyl” and protected choline chloride in the form of rumen protected choline (RPC). The materials used were 15 male Brahman Cross beef cattle aged 18–24 months. The research procedure involved feeding the formulated ration and elephant grass seven times per day at two-hour intervals. The parameters observed included forage intake, concentrate intake, and total feed intake, as well as sub-parameters: relative intake of dry matter (DM), crude protein (CP), total digestible nutrients (TDN), crude fat (CF), and crude fiber (CFiber). The experimental design used was a randomized block design with three treatments and five blocks based on body weight. The results showed that supplementation with Soyxyl and rumen-protected choline (RPC) did not have a significant effect (P>0.05) on forage intake, concentrate intake, total feed intake, or on the sub-parameters of dry matter (DM), crude protein (CP), total digestible nutrients (TDN), crude fat (CF), and crude fiber (CFiber) intake. However, numerically, intake was higher in the treatment combining Soyxyl and RPC than in the other treatments. This indicates a biological potential of bypass protein and protected choline supplementation in enhancing metabolic activity in cattle, although the supplementation levels used in this study were not sufficient to produce statistically significant differences. Therefore, it can be concluded that supplementation of Soyxyl and RPC at the levels used did not significantly affect the feed intake performance of male Brahman Cross beef cattle aged 18–24 months.